A comparison study of the photocatalytic efficiency of different developed photocatalysts/polymer composites. (5th December 2022) - Benltifa, Mahmoud; Brahmi, Chaima; Dumur, Frédéric; Limousy, Lionel; Bousselmi, Latifa; Lalevée, Jacques
Graphical abstract: Highlights: New photocatalyst/polymer composites are proposed. The obtained shaped photocomposites are obtained by photopolymerization. A comparison of photocatalyst/polymer composites efficiency is provided. The MIL-100(Fe)/polymer composite was selected as the most efficient system. Abstract: Polyoxometalates (POMs), Metals Organic-Frameworks (MOFs), Perovskites and Metal Oxides are promising crystalline materials that have received increasing attention due to their impressive photocatalytic performances. However, these catalysts are generally produced in powdered form limiting their reuse and recyclability. A recent solution consisted of associating them with an acrylate polymer via a simple, green and rapid photopolymerization process under visible light irradiation. The obtained shaped photocomposites exhibited at the same time an excellent polymer robustness, stability and malleability while maintaining remarkable photocatalytic properties. The fruitful incorporation of the different crystallites into polymer matrixes are already reported in the literature in our previous works and the chemical mechanisms were also given. However, in order to select the most performant photocatalytic system, which could be probably applied in future technological environmental applications, it is important to compare the photocatalytic efficiency of the different and recently developed photocomposites. Moreover, a comparison with the benchmark catalyst TiO2 is also provided for a better evaluation of their performance. Markedly, some of the reported catalysts were significantly better than TiO2 . The absorption properties, the reusability and the thermal properties as well as the mechanical stabilities were taken into account during the in-depth comparison. The MIL-100(Fe)/polymer composite was selected as the most efficient photocatalytic system, which is also reusable during 10 successive catalytic cycles with an observed little decrease in the pollutants final degradation percentages starting from the 8th cycle. Moreover, this Fe-based MOF immobilized photocatalyst is characterized by interesting mechanical and thermal stabilities as well as a good absorption property allowing its application under visible light irradiation.